2015
DOI: 10.1515/hepo-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Antiradical activity and amount of phenolic compounds in extracts obtained from some plant raw materials containing methylxanthine alkaloids

Abstract: S u m m a r yRaw materials containing methylxanthine alkaloids such as yerba mate, guaraná, white and green tea, coffee seeds, chocolate and cacao seed powder and extracts obtained from these raw materials were investigated for their antioxidant features and the amount of phenolic compounds. The level of phenolic compounds was measured with the colorimetric method using Folin-Ciocalteu's phenol reagent and antioxidant features was determined with the use of DPPH (2,2-diphenyl-1-picrylhydrazyl radical). Amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Although, the human body produces endogenous antioxidants, it still depends on an adequate supply of exogenous antioxidants in the diet [ 11 , 12 ]. Antioxidants are the most important health benefiting substances in coffee, and coffee drink is a rich source of them [ 11 , 13 ]. Coffee beverages are also a source of minerals in the diet [ 6 , 14 , 15 ], including fluoride, but there are only a few works on it [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although, the human body produces endogenous antioxidants, it still depends on an adequate supply of exogenous antioxidants in the diet [ 11 , 12 ]. Antioxidants are the most important health benefiting substances in coffee, and coffee drink is a rich source of them [ 11 , 13 ]. Coffee beverages are also a source of minerals in the diet [ 6 , 14 , 15 ], including fluoride, but there are only a few works on it [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…From naturally occurring compounds the phenolics and flavonoids have been reported to be the most important chemical compounds responsible for the antioxidant capacity [16]. Furthermore, several studies showed that alkaloids also exerted antioxidant properties [17][18][19]. Up to date there is a little information about antioxidant activities of extracts from CM.…”
Section: Introductionmentioning
confidence: 99%